The Malan Seha Local Wisdom in Preserving Forests in Kapuas Regency, Central Kalimantan, Indonesia - Zulkifli Lubis; Saipul Bahri; Sri Alem Br Sembiring (International Journal of Asia Pacific Studies, 2026)
This study investigates why regulatory and rehabilitative efforts to prevent recurring peatland fires in Kapuas Regency, Central Kalimantan, have failed to create environmentally conscious subjects or to shift local land-burning practices. Despite the implementation of numerous policies and programmes since the 1990s, fire incidents continue to occur. This indicates a persistent gap between state-led environmental governance and local community responses. Drawing on a multi-actor ethnographic approach and the Abductive-Causal-Eventism (ACE) framework, this study examines how regulatory interventions interact with local cultural values, economic rationalities, and lived experiences. Data were collected between 2010 and 2015 through participant observation, in-depth interviews, and secondary materials review. The findings reveal that, rather than fostering internalised environmental responsibility, these interventions have generated fragmented, tactical forms of compliance. This study conceptualises this condition as frictional environmentality, defined as a form of environmental subjectivity characterised by cultural tension and strategic behaviour that emerges when universal environmental goals encounter local socio-cultural realities. Overall, this study contributes to environmentality theory by extending the understanding of how environmental subjects are unevenly formed in contexts of contested governance. It also offers insights for designing more culturally embedded and participatory approaches to peatland fire governance in Indonesia.